Subjective Well-being of Tarim Women: A Study of Asceticism in the Novel Bidadari Bumi - Nur Chamidah (Penerbit Hellow Pustaka, 2025)
This research examines the subjective well-being of Tarim women reflected in the novel Bidadari Bumi by Halimah Alaydrus by using the approach of Ed Diener's subjective well-being theory and Max Weber's concept of asceticism. Using descriptive qualitative research method, this study aims to reveal how the subjective well-being of Tarim women is represented in contemporary literary works, as well as to analyze its relationship with asceticism values that are an integral part of Tarim people's lives. The research data was obtained through close reading of the novel, focusing on narratives and dialogues that describe the emotional experiences, life satisfaction, and religious practices of the female characters. The results show that the subjective well-being of Tarim women is formed through a complex interaction between life satisfaction based on spiritual values, positive affect derived from religious observance, and the practice of asceticism that is internalized in daily life. The findings provide a new perspective on how traditional values and modernity can coexist in shaping women's psychological well-being in the context of a traditional Muslim society.